Response of Different Sources of Phosphate Fertilizers and Homo-brassinolide on Total Chlorophyll Content, Yield Attributes and Yield of Hybrid Rice under Lateritic Zone of West Bengal, India - Pramanik, K.; Bera, A. K.; Panda, D. (International Journal of Bio-resource and Stress Management, 2023)
A pot culture experiment was conducted during kharif season of 2009 and 2010 at Agricultural research farm, Visva-Bharati, Sriniketan, Birbhum. The experiment was laid out in CRD with two sources of phosphatic fertilizers, viz. DAP and SSP, two hybrids, viz. PHB71 and 25P25 and two sprayings of homo-brassinolide, viz. panicle initiation (PI) and PI+flowering. The crop was fertilized with respective dose of 150:60:60 NPK kg ha-1. Between the hybrids, PHB71 recorded significantly higher total chlorophyll content, number of effective tillers hill-1, panicle length, test weight, number of filled grains panicle-1, fertility%, straw and grain yield hill-1 and harvest index as compared to rice hybrid 25P25. The percentage increase in grain yield of PHB71 as compared to 25P25 was 28.32. Application of DAP significantly increased total chlorophyll content, number of tillers hill-1, panicle length, test weight, number of filled grains panicle-1, fertility(%), straw and grain yield hill-1. Two spraying of homo-brassinolide at PI and flowering significantly increased yield attributing parameters, fertility%and grain yield hill-1 as compared to one spraying of homo-brassinolide at PI stage